Exploring the behavioral component of the behavioral immune system through the cyberball game - Machado, Roberto Carlos Vilas (2021)
The Behavioral Immune System is a complex suite of psychological mechanisms designed to protect the organism from potentially dangerous microorganisms, through emotional, cognitive, and behavioral strategies. This research proposes that, under a potential contamination situation, humans are guided to adopt avoidance behavior strategies towards the potential source of contamination. This was tested using an online game known as Cyberball, a ball-tossing game where three players must throw a ball to each other. Different participants played the game with different virtual players who differed on their health status. In particular, different groups of participants played the game with one healthy and one sick virtual player; two healthy virtual players; or two sick players. We hypothesized that participants on the healthy-sick game condition would avoid tossing the ball to the sick player, while participants on a condition of equal descriptors would not report differences on tosses. Moreover, we explored if the response of participants were based on reciprocity (rather than on the associated descriptors) and on the number of throws received from the virtual players. Our results revealed that participants who have been set to play with both sick virtual players (running nose vs. diarrhea), completed one part of the game and received an equal number of throws from the virtual players, displayed heightened avoidance behavior towards the first player, and reciprocated more often to the second player. On the other hand, when participants received the ball a different number of times from each player, or completed the game, no significant effects were obtained. Our study suggests that the Cyberball game can be used to explore the behavioral component of the Behavioral Immune System. Furthermore, our findings contribute to understand how human behavior is guided to overcome when set on a potential contamination of disease condition.